Landscape-ecological carcass model of urban landscape and methods of optimize urban landscapes (on the patterns of Ganja and Mingachevir cities) - Hajiyeva, Afag; Hajiyeva, Gulnar; Dadashova, Khumar Khanim (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
State of the problem. The article outlines the natural and anthropogenic foundations of urban landscapes and the organization and modeling of ecological carcasses. Currently, the impact of human activity in the area, on the landscapes, especially on urban landscapes, sometimes leads to the fundamental change and reconstruction of several landscape units or components, the degradation of the sensitive ecosystems of the area, and the creation of completely anthropogenic complexes.Object learning. The main object learning is as follows; study of the differentiation characteristics of the factors influencing the formation of modern geosystems (relief, climate, hydrological and hydrogeological conditions, etc.), researching eco-geographical problems caused by anthropogenic changes, drawing up a map with appropriate content on a large scale, structural and functional characteristics of modern natural geosystems spreading in the research area, exposure to severe anthropogenic influences, study of ecological problems, studying the structural-functional aspects, levels of anthropogenic loading and assimilation, as well as the ecological condition of the modern natural geosystems spreading in the research area, complex study of optimization and large-scale ecological stability, drawing up of ecological potential assessment maps of landscapes.The purpose of this study is the landscape ecological formation of urban landscapes in the Republic of Azerbaijan, the optimization of urban landscapes, the analysis and generalization of urban development processes at the level of urban creation and living environment, and the determination of the main regularities of the formation of this environment, taking into account innovation and traditional processes.Methodology. Ecological analyses were carried out on relevant urban landscapes, and four environmental hazard zones were identified in Ganja, and three in Mingachevir (1: 20000) scale ecological risk maps were drawn up. In the end, the principles of the organization of "ecosystems" based on the optimization of both urban landscapes were analyzed.Research results. The degree of anthropogenic disturbance of the territory was determined, and a map-scheme of the ecogeographic assessment of landscape complexes was drawn up. The study of anthropogenic changes in natural landscapes and the evaluation of the anthropogenic impact in percentage according to digital electronic map fragments was carried out. In the ArcGIS program, the inclination and exposure of slopes in the area, the hypsometry of the relief in the area, the density of roads, the ecogeographical condition of modern urban landscapes, risk zones, and optimization of urban landscapes, etc. maps have been drawn up.The scientific novelty of the research. The importance and functional role of the city as a complex living environment for the country's population is defined. In the process of city planning in the Republic of Azerbaijan, the face of the city, the composition system of urban architecture, innovations, and traditional features are determined. The main city-forming function and role of the river were determined in the studied cities. And the linear features of the development of the cities, and the differences in formation were determined and analyzed. Accordingly, each of the cities has its own unique development models. Environmental problems of cities were investigated and environmental risk and optimization maps were drawn up.